2017
DOI: 10.1038/cddis.2017.512
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoprotein enriched in diabetes (PED/PEA15) promotes migration in hepatocellular carcinoma and confers resistance to sorafenib

Abstract: Hepatocellular carcinoma (HCC) is the third-leading cause of cancer-related death with limited treatment options and frequent resistance to sorafenib, the only drug currently approved for first-line therapy. Therefore, better understanding of HCC tumor biology and its resistance to treatment is urgently needed. Here, we analyzed the role of phosphoprotein enriched in diabetes (PED) in HCC. PED has been shown to regulate cell proliferation, apoptosis and migration in several types of cancer. However, its functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 52 publications
5
27
0
Order By: Relevance
“…CDDP treatment and PE-15 depletion resulted in significant decreases in the percentage of BrdU-positive cells, and CDDP treatment further reduced the percentage of BrdU-positive SGC7901-PEA low cells, compared with the controls (data not shown and available upon request). Previous studies have revealed that PEA-15 promotes cell proliferation by regulating ERK phosphorylation (9,25). As revealed in Fig.…”
Section: Pea-15 Depletion and Cddp Inhibits Cell Proliferation Bymentioning
confidence: 79%
See 3 more Smart Citations
“…CDDP treatment and PE-15 depletion resulted in significant decreases in the percentage of BrdU-positive cells, and CDDP treatment further reduced the percentage of BrdU-positive SGC7901-PEA low cells, compared with the controls (data not shown and available upon request). Previous studies have revealed that PEA-15 promotes cell proliferation by regulating ERK phosphorylation (9,25). As revealed in Fig.…”
Section: Pea-15 Depletion and Cddp Inhibits Cell Proliferation Bymentioning
confidence: 79%
“…As a multifunctional phosphoprotein, PEA-15 has displayed an important role in several cancer entities (6)(7)(8)(9), but its expression and function have not yet been investigated in gastric cancer. The present study demonstrated that PEA-15 was overexpressed in gastric cancer tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two medications in the first line: Sorafenib, a multikinase inhibitor and Lenvatinib, a multitarget tyrosine kinase VEGFR and FGFR inhibitor, are currently used for the treatment of advanced HCC. [8][9][10] Possible mechanisms inducing resistance to Sorafenib are thought to be autophagy and other pathways 11,12 ; however, precise mechanisms remain elusive. First-line and second-line chemotherapeutic agents, such as Lenvatinib, Pembrolizumab, Ramucirumab, Regorafenib and Cabozantinib, have been approved in an accelerated rate by the FDA in the latest 3 years.…”
Section: Discussionmentioning
confidence: 99%